ANALISIS PENGARUH PROMOSI TERHADAP PENJUALAN PADA UNIT TOKO GROSIR BADAN USAHA MILIK DESA BOJONGKULUR TELADAN MANDIRI (BUMDESA BTM) (Fakultas Ekonomi dan Bisnis Universitas Faletehan, 2024)
This research aims to determine the implementation of promotions carried out by the BUMDesa BTM Wholesale Shop unit, as a wholesale sales business unit, to find out the correlation between promotions and sales, to find out how much the contribution of promotional costs influences sales results, and how big a role or influence is caused by the implementation of promotions. towards increasing sales volume. This research uses primary data from Business Unit Reports as well as direct observations of Business Unit operational activities. Using research methods with descriptive statistical techniques with Correlation Analysis Method, Determinant/Determinant Coefficient Analysis, Correlation Significance Test, Simple Linear Regression Analysis Method, and Regression Coefficient Signification Test. The results of the research show that from the Correlation Analysis calculations, a positive correlation coefficient (r) value of 0.84 is obtained, which means the correlation between promotional costs and sales results is very strong and positive. From the calculation of the Determining Coefficient Analysis, it shows that the contribution of promotional activities to sales results or business income is 70.56%, which means that the contribution of promotional costs is very significant to the sales results of the business. From the Correlation Significance Test, the calculated t value is 2.684, greater than the t table of 2.353, which means the relationship between the independent variable (promotional costs) and the dependent variable (sales results) is strong and significant. And from the calculation of Simple Linear Regression Analysis and Regression Coefficient Signification Test, it is known that the t-count is 2,735, when compared with the t-table with an error rate of 5% or a confidence level of 95% and dk = 3, namely: 2,353, then the conclusion is that t-count is greater than t-table, which means there is a strong and significant influence between promotional costs and sales results.